Dietary Patterns, Body Composition, and Bone Health in New Zealand Postmenopausal Women - Ilesanmi-Oyelere, Bolaji L.; Coad, Jane; Roy, Nicole C.; Kruger, Marlena C. (Frontiers in Nutrition, 2020)
Nutrition affects bone health status. However, analysis of the dietary patterns gives insights into which particular combination of foods may influence nutritional status and bone health. The aim of this study was to explore the associations between dietary patterns, bone mineral density (BMD) and T-scores, and body composition in New Zealand postmenopausal women. This cross-sectional study examined 125 postmenopausal women aged between 54 - 81 years. Body composition, BMD and T-scores were determined using dual-energy X-ray absorptiometry (DXA). Diet composition was assessed using a validated food frequency questionnaire (FFQ) composed of 108 food items, from which 34 food groups were created. Dietary patterns were identified by principal component analysis. The bone and body composition data including skeletal sites T-scores, waist circumference, BMI and body fat percentage were regressed onto the dietary patterns. Four dietary patterns were identified; the milk and milk-based beverages dietary pattern, the dessert, cheese and red meat dietary pattern, the fruit-rich, biscuit and crackers dietary pattern and the oily fish, sports drink and seafood-rich dietary pattern. The milk and milk-rich beverages dietary pattern was significantly positively associated with spine T-score (r = 0.247, P = 0.008), and whole-body BMD (r = 0.182, P = 0.051). The oily fish, sports drink and seafood-rich dietary pattern was negatively associated with waist circumference (r = -0.157, P = 0.094), body mass index (r = -0.163, P = 0.081) and body fat percentage (r = -0.247, P = 0.008). A dietary pattern characterized by a high factor loading of milk and milk-rich beverages was positively associated with whole-body BMD and spine T-score, while the oily fish, sports drink, seafood-rich dietary pattern was inversely associated with total body fat percentage. Consumption of milk, even with coffee showed a positive association with bone health among postmenopausal women. Further intervention research is warranted to confirm relationships between dietary patterns and skeletal sites such as hip and femoral neck T-scores.